(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Several satellite data receiving and distributing centers across the world support data storage, processing and retrieval based on satellite, sensor, product, latitude, longitude, data and time, tec. These systems address queries on satellite products that are mostly high level concepts. A more sophisticated retrieval system that supports ontological concepts, sub concepts and concept hierarchical queries delivers refined results that broaden the scientific horizon of the application domain. This paper deals about the meteorology data deployment in thredds server, ontology management system for meteorology data.